Study on the SDN‐IP–based solution of well‐known bottleneck problems in private sector of national R&E network for big data transfer. (12th November 2017) - Park, Hyoungwoo; Cho, Buseung; Hwang, Il‐sun; Lee, Jongsuk Ruth
Summary: Last‐mile bottleneck, fire‐wall bottleneck, and internal network congestion bottleneck are well‐known performance bottleneck problems of private sector in national R&E network since Internet is adopted for R&E network. The emergency of big data science makes these problems more severe because a famous scientist under such a circumstance is severely restricted in his/her big data R&D. Therefore, government cannot leave these stubs in the realm of a private organization any longer. We, KREONET (Korea Research Environment Open Network), tried to solve these problems by SDN‐IP (software‐defined network—Internet protocol) based on ONOS (Open Network Operation System); SDN‐IP is the leading technology for the softwarization of network, and it is developed by On Lab. KREONET began to deploy SDN‐IP as a tool for the softwarization of Korea R&E network even though others studied to business its' feature for the enhancement of resource management of data center first. The initial goal during the construction of SDN‐IP for KREONET is to solve well‐known problems in R&E network, which are related with last‐mile, fire‐wall, and internal network congestion. These 3 problems are not solved for a long time because it costs too much when we try to solve them by the way of the existed hardware networking. In this paper, we introduce our experience that can catch two rabbits at the same time. These experiences are about the provision of the initial popular service of SDN‐IP with the solution of those well‐known bottleneck problems and about the economic way of SDN‐IP construction by incremental hybrid networking of legacy Internet and SDN‐IP.